2018
DOI: 10.1111/dom.13263
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year long‐term clinical outcome after bariatric metabolic surgery: A multi‐ethnic Asian population in Singapore

Abstract: Bariatric surgery is an effective treatment for morbid obesity and its metabolic related comorbidities; type 2 diabetes, hypertension and hyperlipidaemia. However, the literature is scarce regarding the long-term outcome after bariatric surgery, especially among multi-ethnic Asian populations. Considering the growing number of bariatric metabolic surgeries in Asia, we have attempted to provide a regional perspective on 5-year long-term clinical outcomes post bariatric surgery in Singapore. Between 2010 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…Further validation in other ethnic groups will be of interest. Despite this, the current literature, including Africans Americans, Caucasians, or different Asian ethnic groups, displays no general effect of ethnicity in T2D remission after BS (47,48).…”
Section: Discussionmentioning
confidence: 78%
“…Further validation in other ethnic groups will be of interest. Despite this, the current literature, including Africans Americans, Caucasians, or different Asian ethnic groups, displays no general effect of ethnicity in T2D remission after BS (47,48).…”
Section: Discussionmentioning
confidence: 78%
“…In western countries, research evidences support the consensus that postoperative body weight decreases to a trough at 12–36 months after bariatric surgery ( 3 5 ). However, there is currently no published investigation on standardized weight loss after bariatric surgery in Asian settings, except a few studies in Japan and Singapore showed that the average percent total weight loss (%TWL) following bariatric surgery was 20–25% within the first 3 years ( 6 , 7 ). On account of differences in the baseline body height and weight, and body composition, it is not completely grounded to interpret the weight loss on the Asian communities according to westerner physical standards.…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery is currently considered as one of the most effective therapies for morbidly obese patients since approximately 30% of initial weight of patients is reduced and their weight loss is maintained for 10 to 15 years after the surgery . Evidence has also suggested that bariatric surgery can ameliorate metabolic syndromes, as well as help patients achieve diabetes and other metabolic disorders remission . Around 75% to 90% of patients who underwent bariatric surgery achieved comorbidity resolution, particularly for patients with insulin resistance, hypertension, and respiratory disorders .…”
Section: Introductionmentioning
confidence: 99%
“…4 Evidence has also suggested that bariatric surgery can ameliorate metabolic syndromes, as well as help patients achieve diabetes and other metabolic disorders remission. [5][6][7] Around 75% to 90% of patients who underwent bariatric surgery achieved comorbidity resolution, particularly for patients with insulin resistance, hypertension, and respiratory disorders. 4 Though relapse in recovered patients may occur over time, the long-term effect of bariatric surgery on disease remission was supported by a systematic review, where 66.7% of T2DM patients, 38.2% of hypertensive patients, and 60.4% dyslipidaemia patients achieved disease remission at up to 5 years after bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%